Strategy for the development of Arabica Coffee agribusiness in Cisantana Village, Cigugur District, Kuningan Regency - Hidayat, Edi; Fahmi, Ziad; Faqih, Achmad; Hidayat, Yayat Rahmat (International Journal Labs, 2025)
The purpose of this research is to identify the external and internal factors influencing the development of Arabica coffee agribusiness in Cisantana Village, Cigugur District, Kuningan Regency, and to explore alternative strategies that can be implemented for the advancement of this agrobusiness in the village. This research focuses on the development strategies for the Arabica Coffee Agribusiness. In this research, the population consists of all farmers in the Village, numbering 80 individuals. The sample for internal respondents is based on the Slovin formula. The internal factor analysis matrix (IFAS) for the development strategy for Arabica agbusiness shows that the strength indicator is the volume of production for development activities. The external factor analysis summary (EFAS) strategy shows that there is a gap in the existing literature on the coffee sector by focusing on the unique socio-economic conditions specific to the village, which have not been thoroughly examined in broader studies like those by Summase et al.